2000
DOI: 10.1046/j.1439-0310.2000.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest, but Not Egg, Fidelity in a Territorial Salamander

Abstract: Egg recognition and subsequent egg brooding are costly forms of parental investment in many species of vertebrates. Life history factors, such as coloniality or risk of brood parasitism, may constrain egg recognition in vertebrates. Female red‐backed salamanders (Plethodon cinereus) from my study site are territorial and do not share nest sites with other females. They are terrestrial and neither they nor their eggs are likely to be displaced by environmental factors such as flooding. I experimentally tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 37 publications
(51 reference statements)
0
34
2
Order By: Relevance
“…Parental‐caring animals should have mechanisms through which to locate their eggs if they become separated from them (Peterson, 2000). Despite foraging outside of the nest during the extended period of parental care (up to 35 days; Huang, 2007), nest‐guarding long‐tailed skinks cannot recognize their own eggs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental‐caring animals should have mechanisms through which to locate their eggs if they become separated from them (Peterson, 2000). Despite foraging outside of the nest during the extended period of parental care (up to 35 days; Huang, 2007), nest‐guarding long‐tailed skinks cannot recognize their own eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite foraging outside of the nest during the extended period of parental care (up to 35 days; Huang, 2007), nest‐guarding long‐tailed skinks cannot recognize their own eggs. Peterson (2000) suggested that if the probability of confusing a neighbour’s nest for one’s own nest is small, then indirect nest recognition mechanisms are favoured; but if nests are aggregated or difficult to identify based on environmental cues, direct egg recognition mechanisms are favoured. For example, red‐backed salamanders ( Plethodon cinereus ) cannot discriminate between their own eggs and those of unfamiliar females but can relocate experimentally displaced nest sites (Peterson, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, females are infrequently displaced, and when they return to their nesting cavity they are not forced to choose between their own and conspecific eggs. As a consequence, egg discrimination does not appear to have evolved in woodland plethodontids (Peterson 2000). The behavioral differences we observed in Desmognathus are more problematic.…”
Section: Discussionmentioning
confidence: 99%
“…These broad generalizations were challenged by Peterson (2000) who demonstrated that female Redback Salamanders ( Plethodon cinereus ) exhibit nest, but not egg fidelity. In light of her carefully controlled experiments, we acknowledge that egg recognition may not be ubiquitous among plethodontid salamanders, and we feel that it is time for a comprehensive re‐examination of homing to the nest and egg recognition in Desmognathus .…”
Section: Introductionmentioning
confidence: 99%